Early outcomes of alcohol septal ablation for hypertrophic obstructive cardiomyopathy. Issue 1 (7th November 2013) - Veselka, Josef; Lawrenz, Thorsten; Stellbrink, Christoph; Zemanek, David; Branny, Marian; Januska, Jaroslav; Sitar, Jan; Dimitrow, Pawel; Krejci, Jan; Dabrowski, Maciej; Mizera, Stanislav; Bartel, Thomas; et al.
<x xml:space="preserve">Abstract</x> Background: This study was designed to evaluate the outcomes of alcohol septal ablation (ASA) under multicenter and multinational conditions. Methods: Data for 459 patients (age 57 ± 13 years) from nine European centers were prospectively collected and retrospectively analyzed. Results: ASA led to a significant reduction in outflow gradient (PG) and dyspnea [median of PG from 88 (58–123) mm Hg to 21 (11–41) mm Hg; median of NYHA class from 3 (2–3) to 1 (1–2); P < 0.01]. The incidence of 3‐month major adverse events (death, electrical cardioversion for tachyarrhythmias, resuscitation) and mortality was 2.8% and 0.7%, respectively. Permanent pacemakers for post‐ASA complete heart block were implanted in 43 patients (9%). Multivariate analysis identified higher amount of alcohol (however, in generally low‐dose procedures), higher baseline left ventricular ejection fraction and higher age as independent predictors of PG decrease ≥50%. Conclusions: The results of the first European multicenter and multinational study demonstrate that real‐world early outcomes of ASA patients are better than was reported in observations from the first decade after ASA introduction. © 2013 Wiley Periodicals, Inc.